Gait evaluation in hip osteoarthritic and normal dogs using a serial force plate system - Kennedy, S.; Lee, D. V.; Bertram, J. E. A.; Lust, G.; Williams, A. J.; Soderholm, L. V.; Hamilton, S.; Bliss, S. P.; Dykes, N. L.; Todhunter, R. J. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
The effect of canine hip osteoarthritis (OA) on vertical force distribution was studied using a serial force platform system. This system allows simultaneous measurement of vertical and horizontal force impulses from each limb of a trotting dog. Using these measurements and novel analysis techniques a complete and precise analysis of load distribution was performed. Load distribution was compared between a group of normal dogs and a group of dogs with radiographic evidence of hip OA. Results of this study indicate that trotting dogs with hip OA redistribute vertical force primarily by shifting force between trotting pairs (side-to-side compensation) rather than within trotting pairs (hind-to-fore compensation).
Keywords: Gait analysis; osteoarthritis; hip dysplasia